INVESTIGATION OF MEASLES OUTBREAK IN A DISTRICT OF BALOCHISTAN PROVINCE, PAKISTAN - Saeed, Abid; Butt, Zahid Ahmad; Malik, Tabinda (Journal of Ayub Medical College Abbottabad, 2015)
Background: Measles is a communicable viral disease which is a major public health problem and a leading cause of morbidity and mortality in the developing countries including Pakistan with implications for outbreaks. An outbreak was reported from Ibrahim Khan Village of Manzari union council (UC), Pishin District by medical officer during polio campaign on 15th April 2014. A team was sent to investigate the outbreak and suggest control measures. Methods: Rapid assessment of outbreak was done by collecting data from house-to-house from April 16th-20th, 2014. Case was defined as a person of any age, resident of village Ibrahim Khan village with non-vesicular maculopapular rash and fever along with one of the symptoms of cough, coryza and conjunctivitis from April 4th-20th,2014. Routine immunization (RI) was assessed through recall and immunization cards and BCG scars were checked. Line list was developed and data was analyzed. Results: Fifty-five cases (attack rate =11.27%) including 4 deaths (Case Fatality Rates=7.27%) were found. Mean age of children was 47 months (4-132Months). Age-group 0-5 years was most affected (n=48, 87.27%). Along-with maculopapular rash and fever. Other predominant symptoms were: coryza (n=52, 95%), conjunctivitis (n=51, 92%) and pneumonia (n=42, 77%). RI status assessment showed that none of these children had been immunized. About 56.36% of the respondents were unaware about RI, 16.36% mentioned that vaccinator had not visited their homes, 14.54% reported that health facility is far away and 12.72% reported that even if they could get access to a health facility, the vaccines were not available. Conclusion: Functionalization of EPI centre, vaccinations of all children and mass education was strongly recommended. Surveillance system for vaccine preventable diseases (VPDs) should be strengthened to prevent such outbreaks. Outreach activity must be carried out regularly to reach scattered population.